Assessment Of Periodontal Health Status Among Diabetes Mellitus and Hypertensive Patients –A Case Control Study - Patil, Arundhati; SR, Ashwinirani; KA, Kamala; Mahajan, Madhura; Suragimath, Girish (Journal of Neonatal Surgery, 2025)
Introduction: Oral health is an important factor which contributes to patients overall health of age groups from childhood to geriatrics. In midlife of human’s common oral problems include gum disease periodontal disease, tooth loss, dry mouth (xerostomia), mucosal lesions and tooth decay, which can be exacerbated by factors like reduced saliva production and multiple medications. With this background the present study was designed to assess the periodontal health status in diabetic mellitus, hypertensive patients and to compare with control group. Materials and Methods: A total 300 patients were recruited for the study which included 100 normal subjects, 100 diabetic Mellitus (type 2) and 100 hypertenisve patients. The through intra oral examination was done using mouth mirror, CPITN –C probe,no 5 explorer, and community periodontal index, loss of atatchement and oral hygiene index was recorded and compared between the three groups. Results: Majority of patient in our study were males and most common age group was 51-60 years. Assessment of community periodontal index showed healthy gingiva more commonly in control subjects, Majority of the diabetic patients were having periodontitis followed by hypertensive patients than the healthy subjects. In majority of diabetic patients loss of attachment was common than the hypertensive and healthy subjects. In our study generalized periodontitis was most common than the localized periodontitis. Conclusion: Oral health status of periodontium was more compromised in diabetic patients followed by hypertensive patients. The physician and dentist together should contribute the control of gingival and periodontal disease by maintaining the oral hygiene and status of diabetes and hypertension in patients.